Whatever Must Be, Must Be: Translating the Imperative in Luke 7.7 - Miller, Robert P. (The Bible translator, 2014)
This article is an analysis of the imperative iathētō in Luke 7.7. It looks at the textual problems regarding the imperative and argues that the future iathēsetai is an attempt at harmonization with Matthew’s version. After making arguments regarding God’s commands and the theme of authority in the text, the author concludes that those translations which render iathētō in the future or permissive senses do not do justice to the force of the imperative. The author suggests the translation, “but say a word and my servant must be healed,” similar to the NET translation.